Attempt to adapt a statistical model for the heterosis effect in maize F1 hybrids depending on the genetic distance of parental forms. - Tomkowiak, Agnieszka; Broda, Zbigniew; Molinski, Krzysztof; Molińska-Glura, Marta (Plant Breeding and Seed Science, 2010)
During the recent years traditional tillage techniques and procedures have been successfully used in combination with the modern molecular technologies. This enables the researchers not only to employ more objective methods of parental material selection, but also shortens the time required to breed a new variant. Many researchers tried to surmise the heterosis effect by examining the genetic distance between two parental lines. The main objective of this work was to display the correlation between the heterosis effect among the F1 generation of maize and the genetic distance between the parental components. Furthermore, an attempt was made to predict the future heterosis effect using mathematical functions. Finding a proof of those correlations would make it possible to select the parental material, used to create a new variation, more effectively and thus to reduce the number of lines tested during the experiment. Hence it would reduce the time needed for the experiments and also significantly reduce the overall cost of the research project. The research displayed that the molecular markers AFLP and RAPD are useful for predicting the formula of a new corn hybrid . They can be also used to group lines according to their origin or parentage, including those having incomplete information about their parentage. For both markers: RAPD and AFLP, the functions that best describe the correlation between the heterosis effect and the genetic distance, were: a third degree polynomial y=a+bx+cx2+dx3 and a linear function y = a + bx...